Facial Basal Cell Carcinoma Treated with Topical 5% Imiquimod Cream with Dermoscopic Evaluation - Singal, Archana (J Cutan Aesthet Surg, 2016)
Basal cell carcinoma (BCC) is the most common skin cancer worldwide. Surgical excision is considered to be the primary therapeutic modality wherever possible. For inoperable cases, 5% imiquimod seems to be a good alternative. We present two cases of nodular pigmented BCCs on the face in elderly women successfully treated with 5% imiquimod cream application resulting in complete clinical clearance of lesion as well as on histology and dermatoscopy. There was no recurrence of the lesion on 2 years follow-up for the first and 1.5 years for the second patient.